2010
DOI: 10.1093/rheumatology/keq171
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of disease activity and progression in Takayasu’s arteritis with Disease Extent Index-Takayasu

Abstract: During follow-up, most TA patients showed no clinical activity with DEI-Tak. Although the agreement between Kerr's criteria and DEI.Tak seemed very good, using Kerr's criteria instead of DEI.Tak increased the consistency with PGA, which could be explained by the influence of imaging data and acute-phase reactant levels on the physician's decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 12 publications
1
61
0
4
Order By: Relevance
“…The global activity criteria, such as National Institute of Health (NIH) criteria, must be viewed with caution given the current lack of validated activity criteria [1,36]. Moreover, the National Institute of Health (NIH) criteria and recently proposed DEI-TAK criteria [1,37] need information regarding new onset or worsening of clinical features during patients' follow-up. However, we assess disease activity without such information at the time of diagnosis because we have to decide whether to treat the patients with immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…The global activity criteria, such as National Institute of Health (NIH) criteria, must be viewed with caution given the current lack of validated activity criteria [1,36]. Moreover, the National Institute of Health (NIH) criteria and recently proposed DEI-TAK criteria [1,37] need information regarding new onset or worsening of clinical features during patients' follow-up. However, we assess disease activity without such information at the time of diagnosis because we have to decide whether to treat the patients with immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%
“…The global activity criteria, such as National Institute of Health (NIH) criteria, must be viewed with caution given the current lack of validated activity criteria [23]. Moreover, NIH criteria and recently proposed DEI-TAK criteria [24] need information regarding new onset or worsening of clinical features such as vascular ischemia and angiographic features during patient's follow-up. However, when we assess disease activity at the time of patient's first presentation, we do not have such information, even though we have to decide whether to treat the patient with immunosuppressives according to the disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Male patients and localized abdominal lesions are frequently seen in southeastern Asia, China, and southern Africa. 2,[10][11][12][13][14][15] Sharma and Jain 16 reported that hypertension and abdominal aortic lesions were observed more frequently in male patients, whereas cervicobrachial vascular involvements were more often seen in female patients. TA has also developed in young people in all countries.…”
Section: Editorial See P 1685 Clinical Perspective On P 1709mentioning
confidence: 99%